An Upper Ediacaran Glacial Period in Cadomia: the Granville tillite (Armorican Massif) – sedimentology, geochronology and provenance. (9th July 2022) - Linnemann, Ulf; Hofmann, Mandy; Gärtner, Andreas; Gärtner, Jessica; Zieger, Johannes; Krause, Rita; Haenel, Robert; Mende, Katja; Ovtcharova, Maria; Schaltegger, Urs; Vickers-Rich, Pat
Abstract: In the Cadomian orogenic belt a package of glacigenic sedimentary deposits have been recently described in the Armorican Massif (Normandy, France). The Granville Tillite Member, the middle part of the upper Granville Formation, is late Ediacaran in age. Maximum depositional ages of the pre- and syn-glacial sedimentary deposits obtained by LA-ICP-MS U–Pb detrital zircon dating indicate a maximum age of 561 ± 3 Ma. Combined with geochronological data on the previously described glacial deposits in Cadomia, West Africa, Arabia and Iran, the Granville Tillite Member appears to represent an Upper Ediacaran Glacial Period in northern peri-Gondwana, clearly younger than the c . 580 Ma old Gaskiers glaciation. Detailed mapping and analysis of the depositional regime of two sections near the city of Granville are indicative of two independent glaciomarine lower and upper tillite deposits separated by a distinct conglomeratic marker horizon, evidently a massive gravel beach horizon deposited during an interglacial stage. Age spectra of detrital zircon U–Pb ages constrain the palaeogeographical position of the upper Granville Formation to the periphery of the West African Craton. Post-Gaskiers aged glaciations in Cadomia and in West Africa should be grouped into an Upper Ediacaran Glacial Period dated at c . 565 Ma. This glacial period seems not to be related to the negative δ 13 C Shuram–Wonoka anomaly. Sedimentary deposits formed during the Upper Ediacaran Glacial Period show a scattered distribution along the marginal orogens of the Gondwana supercontinent independent of palaeolatitude and are coupled most likely to contemporaneous orogenic processes and uplift.